A highly collimated jet from the Red Square nebula MWC 922. Issue 4 (23rd January 2019) - Bally, John; Chia, Zen H
Abstract: Deep, narrow-band H α and 6584 Å [N ii ] CCD images of the peculiar, infrared excess B[e] star MWC 922 reveal a collimated, bipolar jet orthogonal to the previously detected extended nebula. The jet consists of a pair of ∼0.15 pc segments on either side of MWC 922 separated by gaps. The most distant jet segments disappear ∼0.6 pc from the star. The north-west beam points to a faint emission-line feature 1.65 pc from MWC 922 that may be a terminal bow shock where the jet rams the ambient medium. The narrow opening-angle of the jet combined with an estimated internal sound speed of ∼10 km s −1 implies a jet speed ∼500 km s −1 . The previously detected nebula extends up to 0.6 pc to the south-west of MWC 922 at right angles to the jet and appears to be an extension of the compact, edge-on disc surrounding the star. It points towards the H ii region Messier 16 located ∼1° (∼30 pc in projection) to the south-west. This nebula and jet appear to be externally ionized by the ambient Lyman continuum radiation field and have electron densities of n e  ∼ 50–100 cm −3 . The south-west nebula and jet have similar surface brightness in H α and [N ii ]. Faint 70 μm emission traces the south-west ejecta that likely originates from ∼50 K dust embedded in the photoionized plasma which may shadow the dimmer ejecta north-east of MWC 922. MWC 922 may be a massive member of the Serpens OB1 or OB2 associations surrounding Messier 16 and Sh2-54.